2018
DOI: 10.3758/s13415-018-00648-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in emotional perspective-taking: Its effect on the late positive potential

Abstract: Aging is associated with changes in cognitive and affective functioning, which likely shape older adults' social cognition. As the neural and psychological mechanisms underlying age differences in social abilities remain poorly understood, the present study aims to extend the research in this field. To this purpose, younger (n = 30; M age = 26.6), middle-aged (n = 30; M age = 48.4), and older adults (n = 29; M age = 64.5) performed a task designed to assess affective perspective-taking, during an EEG recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 78 publications
(130 reference statements)
10
20
0
Order By: Relevance
“…The results of studies conducted with ERPs point in the same direction, which is the case of a recent study conducted with a ToM task involving pictures of social scenarios (Fernandes et al, 2019).…”
Section: Aging and Theory Of Mindsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of studies conducted with ERPs point in the same direction, which is the case of a recent study conducted with a ToM task involving pictures of social scenarios (Fernandes et al, 2019).…”
Section: Aging and Theory Of Mindsupporting
confidence: 74%
“…In addition to the accuracy rates, the authors assessed how mentalizing abilities modulated the late positive potential (LPP), an ERP that is higher to recognized than to new material (Danker et al, 2008). The LPP was assessed in those trials in which participants gave a correct answer, and results showed that younger adults had higher amplitudes for congruent than incongruent targets, while older adults had similar amplitudes in both conditions (Fernandes et al, 2019). The younger adults' higher amplitudes for congruent targets suggest that they were able to infer the appropriate emotional states during the scenarios, which they maintained in working memory and then compared with the emotion displayed in the target.…”
Section: Aging and Theory Of Mindmentioning
confidence: 99%
“…Exclusion criteria consisted of the presence or history of any cardiovascular, neurological, or musculoskeletal problems contraindicated to exercise, as well as a history of any head injury with a loss of consciousness. Given the potential influence of emerging developmental changes (Lukie, Montazer-Hojat, & Holroyd, 2014) and advancing age (e.g., Fernandes et al, 2019; Mather, 2016) on emotional and reward processing, we restricted our sample to adults between the ages of 18 and 35 years of age. All participants were physically able to engage in aerobic exercise as indicated by responses to the physical activity readiness questionnaire (PAR-Q; Thomas, Reading, & Shephard, 1992).…”
Section: Participantsmentioning
confidence: 99%
“…This hypothesis has motivated the study of patients with chronic pain, mainly regarding the processing of information related to pain. Previous studies have shown that people with chronic pain selectively process information related to their clinical condition to the detriment of neutral information [ 23 , 24 ]. However, other studies have failed to find evidence of possible attentional biases [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the LPP shows a temporally broad distribution (e.g. [ 23 ]), we divided its corresponding time window into an early (LPPe; 400–600 ms) and late component (LPPl; 600–800 ms).
Fig.
…”
Section: Methodsmentioning
confidence: 99%